Publisher Correction: Female mice lacking Ftx lncRNA exhibit impaired X-chromosome inactivation and a microphthalmia-like phenotype. Issue 1 (December 2018) - Hosoi, Yusuke; Soma, Miki; Shiura, Hirosuke; Sado, Takashi; Hasuwa, Hidetoshi; Abe, Kuniya; Kohda, Takashi; Ishino, Fumitoshi; Kobayashi, Shin
In the original HTML version of this Article, the affiliation details for Hirosuke Shiura, Hidetoshi Hasuwa and Takashi Kohda were incorrect, as detailed in the associated Publisher Correction. These errors have been corrected in both the HTML version of the Article.